Accustomed to Computational Thinking Through Gamification of Learning Model. - Shariful Hafizi, Md Hanafiah; Mohd Zaki, Mohd Amin; Kamarul Shukri, Mat Teh; Norzehan, A.Karim (2017)
Gamification involves game-thinking and game mechanics llrocess to eucourage user engagement and influencing thern to solve problems. Camification of education means the use of video game mechanics and dynamrcs as a strategy to inl'use ordinary activities or processes to sllpport 21st centur!'iearning and facilitation process. With lBestariNet (1BN) project, a virtual learning environment (VLE) named Frog was chose to support Malaysian school environment and commut-tit1r. Frog VLE combines conventional education concept rvrth cloud computing technologies. With Frog VLE, leaming and facilitation (pentbelajaran dan pemtdahcaraan, PdPc) can be done ubiquitously tr,venty-four hours daily seven days a week; with computing devices and Intemet connection. Malaysia Ministry of Education (Moli) introdnces a new curricnlum for secondarv school's educalion: Ktrihittm Standard Sekolah MenengcLh (KSSM); on 20'l7. One of the new sr-rbject been introduced ancl rebranding along is lsas Sains Kontptrer; ,4SK (Computer Science Basics) that will be teach to lower secondary students. KSSM ASI( objectives is to prepare students with cornputational thinking knorvledge and skills. Computational thinking is a thinking process which invoives an ability to think, understand, and applying computer-basecl solutions to so1r,e problems effectivel-v. This paper describes a design to apply gamification in ASK, hence promotes motivation, engagement and accustomed students with computational thinking through gamification of leaming ARCS-G n-rodel via Frog VLE.